Antimicrobial stewardship: a Canadian perspective. Issue 3 (5th September 2016) - Rennert-May, Elissa; Conly, John
Abstract : Purpose: – The purpose of this paper is to explore the current state of antimicrobial stewardship implementation and development within Canada at both a federal and provincial level. Design/methodology/approach: – Narrative review. Findings: – There have been several prominent conferences and reports in Canada regarding the development and implementation of antimicrobial stewardship programs over the past two decades. However, despite the knowledge that there is a need for standardization of programs across Canada with accurate mechanisms and infrastructure in place for implementation and evaluation of these programs, there is still a lack of consistency across the country. In addition pharmacy information regarding inpatient and outpatient antimicrobial use is not uniformly reliable. Recently, the Public Health Agency of Canada using the Pan-Canadian Public Health Network as a vehicle organized a task group to help facilitate the working relationships among the provincial, territorial and federal governments in terms of implementing antimicrobial stewardship programs. This network has the potential to enhance and standardize programs across the country. Originality/value: – This paper looks at Canadian policy regarding antimicrobial stewardship at a federal as well as provincial level. Historic conferences, reports and discussions are highlighted emphasizing the progressive changes over the past two decades and highlight many of the challenges that Canada continues to face.